Kinerja Aparatur Sipil Negara Dalam Pelayanan Publik Di Distrik Maladum Mes Kota Sorong - Muhammad Arifin Abd Kadir; Kamaluddin; Arie Purnomo (Jayapangus Press, 2022)
Public services are all activities in the context of fulfilling basic needs by the basic rights of every citizen or resident of goods, services, and administrative services provided by service providers related to the public interest. Therefore, this study aims to determine the efforts to improve employee performance in public services in the Maladum Mes District, Sorong city, West Papua. The research method used is descriptive qualitative. The population is the total number of 15 civil servants within the Maladum Mes District office in Sorong City. Data were collected from questionnaires, interviews, and document reviews. That Service Performance The government administration process in Maladum Mes District, Sorong City is still far from quality, because 1) it still needs and must be improved, namely the appearance and discipline of employees, accuracy and expertise of employees, response and fast and precise service; 2) Factors that hinder the improvement of the performance of the State Civil Apparatus in the Maladum Mes District are the lack of skilled/expert personnel, the lack of staff and discipline on time, the lack of computer and printer support equipment; and 3) Ways to solve problems in improving the performance of the state civil apparatus in the District of Maladum Mes Sorong City, namely by holding training and the need for procurement of office facilities and infrastructure, adding employees and the availability of operational vehicles to support public service work.